Technical Notes: Computational Model for Housing Drainage System Case Study: Kharismatama Permai Housing in Padang - Mera, Mas; Dewi, Yessi Puspita; Saputra, Deri; Monica, Zelfa Lonna (Jurnal Teknik Sipil, 2012)
Abstract. This study is about the development of a computational model, which is capable of simulating flows flowing through roadside gutters in a housing drainage system with a very mild-slope land in a steady state condition. The governing equation of the model is the world-widely used uniform flow formulation by Manning. The equation is solved using the Newton-Raphson method. The resulting model is then applied to simulation of gutter flows flowing across a drainage system of Kharismatama Permai housing in Padang, which is frequently overflowed by the rainfall excess. The rate of rainfall intensity was measured manually at the same time the flood occurred at the considered housing complex. Types of gutter materials were observed to determine the coefficients ofÂ  utter roughness, and types of land covers also were observed to determine the run-off coefficients. By adjusting the gutter slopes and varying the flow directions, the drainage system can flow the rainfall excess without overflowing. Abstrak. Penelitian ini adalah tentang pengembangan sebuah model komputasi yang dapat mensimulasikan aliran yang melewati saluran samping jalan dalam sistem drainase komplek perumahan yang mempunyai lahan yang sangat landai dalam kondisi tidak bergantung waktu. Persamaan pengaturnya adalah persamaan aliran seragam Manning yang telah digunakan secara luas di seluruh dunia. Persamaan tersebut diselesaikan dengan menggunakan metode Newton-Raphson. Model ini diaplikasikan untuk mensimulasikan aliran saluran samping jalan dalam sistem drainase Perumahan Kharismatama Permai di Padang, yang sering banjir akibat sisa hujan. Intensitas curahan hujan diukur secara manual pada waktu yang sama banjir terjadi pada komplek perumahan tersebut. Jenis bahan tubuh saluran diamati untuk menentukan koefisien kekasaran saluran, dan jenis penutup lahan juga diamati untuk menentukan koefisien limpasan. Dengan mengatur kemiringan saluran dan mengubah arah alirannya, sistem drainase tersebut dapat mengalirkan sisa hujan tanpa banjir.